"Justified dependency": Effects of perceived stability of social hierarchy and level of system justification on help-seeking behavior of low-status group members. (July 2014) - Chernyak-Hai, Lily; Halabi, Samer; Nadler, Arie
Recent research on intergroup helping has shown that receiving and seeking help can be a way in which groups assert or challenge the existing hierarchy. The present research, consisting of two studies conducted in the Arab–Jewish Israeli context, examined how the manipulated perceived stability of social hierarchy and dispositional levels of system justification (SJ) influence the willingness of Arab participants to seek assistance from a Jewish helper (representing low- and high-status groups in Israel, respectively). As expected, findings indicate that Arab participants who perceive the social hierarchy as just and stable, show a significantly higher preference to seek dependency-oriented help from Jews. On the other hand, those characterized as low SJs report overall low willingness to seek help from Jewish group members, but show some readiness to seek autonomy-oriented help when status relations between Arabs and Jews are perceived as stable. Theoretical and practical implications for intergroup helping relations are discussed.